2017
DOI: 10.1093/cercor/bhx221
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of AMPAR Rescues Intellectual Disability-Like Phenotype in Tm4sf2−/y Mice

Abstract: Intellectual disability affects 2–3% of the world's population and typically begins during childhood, causing impairments in social skills and cognitive abilities. Mutations in the TM4SF2 gene, which encodes the TSPAN7 protein, cause a severe form of intellectual disability, and currently, no therapy is able to ameliorate this cognitive impairment. We previously reported that, in cultured neurons, shRNA-mediated down-regulation of TSPAN7 affects AMPAR trafficking by enhancing PICK1–GluA2 interaction, thereby i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 87 publications
4
42
0
Order By: Relevance
“…Tetraspanins also bind cholesterol, an interaction thought to mediate their self-association (Charrin et al, 2003a). To date, 33 mammalian tetraspanins have been described to act in cell-cell adhesion, cell motility and proliferation, immunity, and nervous system development (Hemler, 2005), but there is little work on their synaptic function (Bassani et al, 2012;Murru et al, 2017Murru et al, , 2018, thus their supramolecular organization at synapses is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraspanins also bind cholesterol, an interaction thought to mediate their self-association (Charrin et al, 2003a). To date, 33 mammalian tetraspanins have been described to act in cell-cell adhesion, cell motility and proliferation, immunity, and nervous system development (Hemler, 2005), but there is little work on their synaptic function (Bassani et al, 2012;Murru et al, 2017Murru et al, , 2018, thus their supramolecular organization at synapses is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, LHb has been reported to be involved in behavioral flexibility ( Baker and Mizumori 2017 ; Mizumori and Baker 2017 ), sociability ( Benekareddy et al 2018 ), learning and memory ( Lecourtier et al 2004 ; Bromberg-Martin et al 2010 ; Shumake et al 2010 ) that are often impaired in ID and ASD patients ( Moretto et al 2018 ). Here, we report that Tm4sf2 −/y mice, beyond an ID-like phenotype ( Murru et al 2017 a), display altered sociability, increased repetitive behaviors, anhedonic- and depressive-like states. Furthermore, we found that LHb neurons of Tm4sf2 −/y mice show reduced excitability, aberrant neuronal firing pattern and altered sodium and potassium voltage-gated ion channels function.…”
Section: Introductionmentioning
confidence: 85%
“…Coronal slices (thickness, 270 μm) from Tm4sf2 +/y and Tm4sf2 −/y 40–60 days old male mice were prepared as previously described ( Murru et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations